The Effect of Risk Committee Composition on Financial Performance: An Empirical Study on Saudi Banks - Alshehri, Faiz A.; Almulhim, Abdulateif A. (The Arab Journal of Administration, 2024)
The study aimed to investigate the effects of the composition of the risk committee on the financial performance of the banks listed on the Saudi Stock Market. The sample of the study consisted of (10) banks for the period from 2010 to 2020. This study relied on secondary data (panel data), which combines time series data and cross-sectional data. The Pooled OLS model was used to test the hypotheses of the study. The results showed a positive impact of the presence of independent risk committee, the percentage of independence directors of the risk committee, and the percentage of directors who obtained a degree in finance or risk in the committee, on banks performance. On the other hand, the study found a negative relationship between risk committee size and percentage of busyness directors with banks performance. This study confirms that it is important for banks to commit with activating the corporate governance regulations and mechanisms in their operations in general, and to commit with activating the governance practices of the risk committee in particular. This action in turn can contributes to increase the efficiency of banks’ performance and mitigating the overall risks of banks. Regulators also should pay attention to the number of busyness directors in the risk committee and disclose guidance regarding their existence in the committee.